The Effect of Maternal Supplementation of Lutein and Docosahexaenoic Acid on Behavior and Brain Structures in Offspring in a Pig Model (P11-005-19). (13th June 2019) - Fang, Xi; Jeon, Julie; Kinder, Holly; Azain, Michael; Zhao, Qun; Ahn, Jeongyoun; Chung, Hee Cheol; Park, Hea Jin
Abstract: Objectives: Lutein (LUT) and docosahexaenoic acid (DHA) accumulate in the brain and are positively associated with neurocognitive function. Maternal nutritional status in pregnancy and lactation impact the brain development of the offspring. The objective of this study was to determine the impact of maternal supplementation of LUT and DHA during the perinatal period on the cognitive outcomes and regional brain volumes of the offspring. Methods: Pregnant sows (n = 11) were fed a control diet only (CON), CON containing LUT (LUT, 2 mg/kg BW/day), or CON containing DHA (DHA, 75 mg/kg BW/day) from late gestation to lactation period for 60 days. At weaning (21d), piglets (n = 4/litter, total n = 44) underwent open field test (OFT) and object recognition test (ORT) to assess exploratory behaviors and memory formation, respectively. In addition, magnetic resonance imaging (MRI) was performed (n = 12) to measure the volumes of 19 brain regions. Results: In the OFT, piglets from LUT-fed sows showed 96% higher sniffing wall frequency compared to controls ( P = .022), demonstrating that maternal LUT supplementation may enhance the exploratory behavior of its offspring at weaning. In the ORT, male LUT pigs ( P = .034), and both male and female DHA pigs ( P = .016, P = .035, respectively) spent significantly longer time exploring the novel object than familiar object, while controls spent similar time with both objects ( P > .05), suggesting that maternal supplementation with either LUT or DHA during the perinatal period may improve hippocampal-dependent memory formation of the offspring. MRI volumetric assessments showed that piglet brains were composed of 63.4% cortex, 11.39% cerebellum, 2.76% thalamus, 1.84% hippocampus, and 4.63% olfactory bulb and other subcortical regions. Maternal LUT or DHA supplementation did not affect the volumes of these regions except for the internal capsule. The volume of the internal capsule was significantly larger in the DHA pigs compared to controls ( P = .026). Conclusions: Maternal supplementation of LUT or DHA may increase exploratory behaviors and memory function of the offspring at weaning without affecting the volume of major brain structures. Further analysis is ongoing to elucidate the mechanisms of the neurocognitive changes by assessing functional connectivity of brains via functional MRI. Funding Sources: The study was supported by Georgia Experimental Agricultural Station, HATCH #GEO00795 and Faculty research grant from Office or Research at the UGA. DHA was kindly provided by DSM, Inc.